Ultra‐low LOD H2O2 Sensor Based on Synergistic Nernst Potential Effect - Zhaoqun Wang; Wen Gao; Xiaorong Niu; Yuhang Liu; Zichen Jin; Fan Zhang; Zhengdong Cheng; Xiaoning Jiang; Wendong Zhang; Ting Wang; Jianlong Ji; Xiaojie Chai; et al. (Advanced Science, 2025)
Abstract The food processing industry and biomedical science research are relying on the low limit of detection (LOD) for hydrogen peroxide (H2O2). Organic electrochemical transistors (OECTs) are excellent for biochemical sensing applications due to their excellent signal amplification capability. The paper describes  a way of detecting H2O2 through the use of stacked poly(3,4‐ethylenedioxythiophene): bromothymol blue (PEDOT: BTB)/poly(3,4‐ethylenedioxythiophene): polystyrene sulfonate (PEDOT: PSS) as the semiconducting channel of the OECT. The H2O2 sensor presents an ultra‐low LOD, down to 1.8 × 10−12 M, due to the synergistic effect of the Nernst potential generated by the platinum gate electrode catalyzing H2O2 and the Nernst potential generated by the interaction between BTB molecules and hydrogen ions, the by‐product of H2O2 catalysis. A microsystemwith a signal processing circuit and a mobile app for the sensor has been developed, and they are then tested on commercial milk samples to verify their reliability. Since the majority of enzyme‐catalyzed reactions generate or use H2O2 in biochemical reactions, the methodology is applicable not only to the detection of H2O2 but also to the detection of analytes based on enzyme‐catalyzed reactions. For demonstration, glucose detection with a LOD of down to 8.82 × 10−11 M is also presented.